CP-060 An investigation into the impact of a Clinical Ward Pharmacist on medicines returned to Pharmacy for re-use or destruction. (24th February 2014) - O'Connor, S; Byrne, S; Stack, C; Leahy, M; Finnegan, K; Fleming, A
Abstract : Background: The Bon Secours Hospital, Tralee, is a private hospital with 130 inpatient beds. Medicines are dispensed on an individual patient basis The disadvantages of this system are an overall increase in workload and a high level of waste. Purposes: To investigate the volume and cost of medicines returned to pharmacy. To look at the extent to which returned medicines are destroyed or re-entered into pharmacy stock after return. To estimate the impact of a clinical ward pharmacist on the return of dispensed medicines to pharmacy. To recommend changes to the existing dispensing system, to reduce the volume and cost of returned medicines. Materials and methods: This study examined the medicines returned from St. Teresa's ward (no Clinical Ward Pharmacy service) and St. Patrick's ward (has a Clinical Ward Pharmacy service) on a weekly basis during a four week period April to May 2013. The costs of the medicines returned (waste and non-waste) and the cost of the returns procedure were calculated. Results: 77% (471/611) of the medicines returned were destroyed (all oral). There were significantly more returns for destruction from St. Teresa's Ward compared to St. Patrick's ward (Pearson's Chi squared = 10.78, p = 0.001). The cost of the medicines returned was 1682.02 € for re-used intravenous medicines, 419.23 € for re-used oral medicines, 618.27 € and 156.29 € for waste oral medicines from St. Teresa's and St. Patrick's wards, respectively. Conclusions: The introduction of a Clinical Ward Pharmacist can reduce the volume and costs of returning medicines in an individual patient dispensing system. Wards should carry a wider range of high frequency, inexpensive oral medicines as stock, to reduce the necessity to dispense for individual patients. No conflict of interest.